A novel multiple-axis MEMS gyroscope-accelerometer with decoupling frames; Sensor Review; Vol. 39, iss. 5 - Baranov P. F. Pavel Fedorovich; Nesterenko T. G. Tamara Georgievna; Barbin E. S. Evgeny Sergeevich; Koleda A. N. Aleksey Nikolaevich; Tanaka S. Shuji; Tsukamoto T. Takashiro; Kulinich I. Ivan; Zykov D. Dmitry; Shelupanov A. Aleksandr (2019, 2019)
Title screen